A STUDY OF WORD-FORMATION PROCESS IN JARGONS USED ON CHATTING IN DotA - SETIAWAN, ACHMAD FAUZY (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Jargon, Chatting, DotAJargon is commonly used by groups that have similar interest, like trades or profession. In internet world, such as online game, gamers do not communicate directly, but they use chatting language for communication. Through chatting, gamers have their own language that only can be understood by them. This language is considered as unique and very useful to communicate effectively while they playing the game. Therefore, the writer is interested to conduct a study on jargon used in DotA. By taking chatting from online game named, DotA, the writer proposed two problems: (1) What jargons are used on chatting in DotA online game and (2) What are the word processes formed the jargon of DotA online game.This study used qualitative approach regard the writer described language phenomenon comprehensively through the words and language. The writer performeddocument collection in order to obtain data. In collecting document the writer activelyparticipated in several games of DotA. The document refers to any word or expression occurred in the conversation in this case known as chatting during the gameplay which is available to be saved into chat log. The writer stopped collecting the data once it had reached point of saturation.The finding revealed that there are 59 jargons found in chatting. The writer found seven types of word formation processes; acronym, clipping, coinage, blending, borrowing, multiple processes, and conversion. Acronym is found to be the most wordformation processes used due to particular reasons. Generally, acronym is frequentlyfound due to its usage could ease gamers in chatting with keyboard as typing media.It is suggested for the future researchers to have research using other media, such as movie, newspaper, magazines, etc. The result of the research is to attest, that internet world also has its own language for communication that cannot be separatedform society.